Interdisciplinary medication reviews of psychiatric patients – A mixed method evaluation - Dagmar Abelone Dalin; Sara Sommer Holst; Lucif Søemosegaard Dalin; Charlotte Vermehren (Exploratory Research in Clinical and Social Pharmacy)
Background: Patients at psychiatric homes are a vulnerable group with several factors complicating their pharmacological treatment. Psychiatric patients in stable treatment are transferred from specialist care to primary care, which presents new challenges as general practitioners (GPs) may feel that they are not sufficiently trained in prescribing and tapering psychiatric drugs. Medication reviews (MRs) have been seen to improve the appropriateness of pharmacological treatment – especially when performed in interdisciplinary teams. Objective: Thus, the aim of this study was to examine to which extent it was possible to conduct interdisciplinary MRs at a psychiatric home and with patient involvement. The study was a mixed-method evaluation study that included 11 quantitative MRs analyzed by descriptive analysis and 5 qualitative semi-structured interviews analyzed by thematic coding analysis. Results: The MR performance formed the basis of an interview study. The patients' GPs and psychiatrist accepted 32 of the 37 (86 %) recommended changes to the current medication. At six months follow-up, 75 % of changes had been implemented. Three main interview themes and seven sub-themes were identified, covering collaboration between healthcare professionals, patient involvement, and the MR method. Conduction of interdisciplinary MRs was affected by e.g. challenges in the collaboration between GP and psychiatrists and patient involvement. Conclusion: Interdisciplinary MRs for psychiatric patients were seen as beneficial by healthcare professionals and had a high implementation rate of medication changes. In future use of the MR model, the involvement of patients and GPs should be ensured and include a psychiatrist in the MR team.